(untitled) (Acta Scientiarum. Technology, 2018)
Â In this work, we firstly describe conditions for being elastica in Minkowski space E41. Then we investigate the energy of the elastic curves and exploit its relationship with the energy of Bishop vectors belong to that elastic curves E41. Finally, we characterize non-elastic curves in E41 and compute their energy to see the distinction between energies for the curves of elastic and non-elastic case in Minkowski space E41.Mathematics Subject Classifications: 53C41, 53A10. Â